PERILAKU GIZI IBU, POLA ASUH MAKAN, KONTRIBUSI SNACK, DAN STATUS GIZI ANAK USIA PRASEKOLAH - Wardah, Siti Habibah; Ekayanti, Ikeu (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2014)
ABSTRACTThe aimed of this study were to analyze mother’s nutritional behavior, parenting eating pattern, snack contribution and their correlations toward preschool children’s nutritional status. The design of this study was a cross-sectional in Labschool IPB-ISFA, involved 20 subjects of preschool children. The result of this study showed that 45% of mothers had moderate nutritional knowledge. Most of mother’s nutritional attitude and practice were categorized as good (35%) and poor (35%). Snack had the highest contribution to protein adequacy (58.6%). The contribution of snack to energy, fat, carbohydrate, and natrium adequacy were 41.8%, 44.2%, 45.5%, and 53.6% respectively. Most of subjects had normal nutritional status (80%). Mother’s nutritional knowledge and mother’s nutritional attitude was having significant correlation (p<0.05). Mother’s nutritional practices had significant correlation with eating parenting pattern. There were a significant correlations between carbohydrate and protein from snack with nutritional status (p<0.05), whereas energy and fat from snack had no correlation with nutritional status (p>0.05).Keywords: nutritional behavior, parenting pattern, snackABSTRAKTujuan umum penelitian adalah menganalisis perilaku gizi ibu, pola asuh makan, dan kontribusi snack serta hubungannya dengan status gizi anak usia prasekolah. Desain penelitian adalah cross sectional study dengan 20 subjek anak usia prasekolah di Labschool Pendidikan Karakter IPB-ISFA. Sebagian besar pengetahuan gizi ibu masuk kategori sedang (45,0%). Sikap dan praktik gizi ibu subjek paling banyak termasuk dalam kategori baik (35,0%) dan kurang (35,0%). Kontribusi energi dari snack terhadap tingkat kecukupan adalah 41,8%, lemak 44,2%, karbohidrat 45,5%, dan natrium sebesar 53,6%. Kontribusi konsumsi snack terhadap kecukupan protein paling besar yaitu sebesar 58,6%. Sebanyak 80,0% subjek memiliki status gizi normal. Perilaku gizi ibu yang mempunyai hubungan signifikan adalah pengetahuan dengan sikap gizi ibu (p<0,05). Perilaku gizi ibu yang mempunyai hubungan signifikan dengan pola asuh makan adalah praktik gizi (p<0,05). Hubungan signifikan antara protein dan karbohidrat dari snack dengan status gizi (p<0,05), sedangkan energi dan lemak dari snack tidak mempunyai hubungan yang signifikan dengan status gizi subjek (p>0,05).Kata kunci: perilaku gizi, pola asuh makan, snack